The Utopian thought of Amilcar de Sousa, an early 20th-century Portuguese naturist and dietitian - Reis, José Eduardo (Cadernos de Literatura Comparada, 2017)
Utopian thinking and literary discourse have dealt in various ways, either romantically or critically, with the issue of "the good life" based on norms of diet and hygiene that respect the environment and the rights of nonhuman species. This perspective intersects with one of the main trends recently pursued by food studies, which has emphasised the link between the need for humans to produce and consume food (on the one hand) and the ethical imperative to abandon humankind’s hegemony over the whole of nature (on the other). The latter prescription stems from an ethical awareness that is not limited to or regulated by a merely anthropocentric and individualistic worldview. In the context of global and contemporary post-industrial society, such awareness would presuppose on humankind’s part a wider and more inclusive approach to the well-being of other species and of nature in general, along with the application of space-time references that are not limited to local geography and contemporary generations. It is in this light that the present paper proposes to discuss the utopian content of two essays on alternative food and living habits, Naturism (1912) and Art of Living (1934) by the “moral revolutionary” Amílcar de Sousa, first President of the Portuguese Vegetarian Society that was founded in Porto, in the early 20th century.